2015
DOI: 10.1175/jhm-d-14-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Hydrological Models via Cross-Spectral Analysis: Case Study of the Thames Basin, United Kingdom

Abstract: Nine distributed hydrological models, forced with common meteorological inputs, simulated naturalized daily discharge from the Thames basin for . While model-dependent evaporative losses are critical for modeling mean discharge, multiple physical processes at many time scales influence the variability and timing of discharge. Here the use of cross-spectral analysis is advocated to measure how the average amplitude-and independently, the average phase-of modeled discharge differ from observed discharge at daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…The model performance was poor and only for one catchment the Nash Sutcliffe efficiency for the optimized simulations was higher than 0.5. Weedon et al (2015) applied nine distributed hydrological models, including JULES, to simulate the daily runoff at the Thames catchment. The evaluation was based on the cross‐spectral analysis and they found that JULES’ performance depended on the configuration that was used (i.e., JULES‐TOPMODEL, JULES‐PDM, JULES) with JULES‐TOPMODEL producing a slightly better performance.…”
Section: Introductionmentioning
confidence: 99%
“…The model performance was poor and only for one catchment the Nash Sutcliffe efficiency for the optimized simulations was higher than 0.5. Weedon et al (2015) applied nine distributed hydrological models, including JULES, to simulate the daily runoff at the Thames catchment. The evaluation was based on the cross‐spectral analysis and they found that JULES’ performance depended on the configuration that was used (i.e., JULES‐TOPMODEL, JULES‐PDM, JULES) with JULES‐TOPMODEL producing a slightly better performance.…”
Section: Introductionmentioning
confidence: 99%
“…10. If a time series is 15 compared to itself, but offset by a few time steps, there is a resulting trend in the high frequency part of the phase difference spectrum (equation A10 in Weedon et al, 2015). The theoretical phase difference trends that approximate the results are shown using black dashed lines in Fig.…”
Section: Performance At Non-daily Time Scalesmentioning
confidence: 89%
“…In order to further assess the model performance at time scales longer than daily and relevant for the studied catchments, and reinforce findings using NS at the daily time scale and mean bias, we use a cross-spectral analysis (Weedon et al, 2015) that provides measures on how the average amplitude and phase of modelled river flow differ from observed river flow at those time scales.…”
Section: Set Of Experiments and Metricsmentioning
confidence: 99%
See 2 more Smart Citations